1989
DOI: 10.3109/00498258909034677
|View full text |Cite
|
Sign up to set email alerts
|

The percutaneous fate of the rodenticide flocoumafen in the rat: Role of non-biliary intestinal excretion

Abstract: 1. Appreciable penetration of radioacticity occurred through rat skin following percutaneous administration of 14C-flocoumafen. At 7 days after dosing 12% of the administered radioactivity remained at the site of application, while 25% was located in the liver as unchanged flocoumafen. 2. Excretion of flocoumafen metabolites via the urine accounted for 10% dose over the 7 day experiment, this is some 30-fold greater than that seen after a single oral dose. 3. Unchanged flocoumafen comprised the major product d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In these reports, systemic effects (coagulopathies, occasionally with fatal outcome) were described, and skin was considered as a portal of entry of anticoagulants into systemic circulation. Percutaneous absorption studies revealed that around 12% of the applied dose of a second-generation hydroxycoumarin, flocoumafen, remained in the skin of rats for up to 7 days (Huckle et al, 1989), and a significant amount of coumarin remained in human and rodent skin for 72 h following its in vitro application (Beckley-Kartey et al, 1997). These data implicate the skin as a place where these agents might linger and possibly exert their effects.…”
Section: Introductionmentioning
confidence: 94%
“…In these reports, systemic effects (coagulopathies, occasionally with fatal outcome) were described, and skin was considered as a portal of entry of anticoagulants into systemic circulation. Percutaneous absorption studies revealed that around 12% of the applied dose of a second-generation hydroxycoumarin, flocoumafen, remained in the skin of rats for up to 7 days (Huckle et al, 1989), and a significant amount of coumarin remained in human and rodent skin for 72 h following its in vitro application (Beckley-Kartey et al, 1997). These data implicate the skin as a place where these agents might linger and possibly exert their effects.…”
Section: Introductionmentioning
confidence: 94%
“…However, there are no published estimates of the hepatic half-life of BR or FL in possums. Hepatic half-life estimates available for Norway rats, 170 days for BR (Parmar et al 1987) and 220 days for FL (Huckle et al 1989), suggested both SGARs may also have a relatively prolonged persistence in possum liver.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic fate studies conducted in rodents (Huckle et al 1988(Huckle et al , 1989a(Huckle et al , 1989b and non-rodent species (Huckle et al 1989c) show that ftocoumafen is absorbed and is extensively distributed within the body, accumulating appreciably in the liver. The hepatic ftocoumafen residue exhibits a long half life in rodents (in rats 220 days) and fowl and is not readily metabolised.…”
Section: Introductionmentioning
confidence: 99%